ALTERNATIF PEMBIAYAAN YANG ADIL DAN SESUAI PRINSIP SYARIAH UNTUK ATASI KESULITAN FINANSIAL - Abdul Haris Perwiranegara; Chavid Moyo Jaladri; Didik Setiawan (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2025)
This article examines fair and Sharia-compliant financing alternatives as a solution for individuals and entities experiencing financial difficulties. Given the high demand for ethical and sustainable financing access, this analysis focuses on Sharia instruments such as Islamic pawnbroking, designed to minimize the risks of riba (interest) and gharar (uncertainty). In addition, this paper highlights the importance of Sharia financial education and the role of Islamic financial institutions in providing inclusive, transparent, and community economic empowerment-oriented products and services. The main objective of this research is to provide a comprehensive understanding of accessible and effectively implementable Sharia financing options to address financial challenges while adhering to the values of justice and blessings. The result of this research is that Islamic pawnbroking certainly not only focuses on how to maintain the existence of its entity but also pays attention to customer satisfaction by receiving input from the community regarding community constraints and needs so that the existence of such Islamic financial institutions is in accordance with community needs.